A Tale of Drug Discovery: Synthesis, Bioassay, and Computational Docking Studies of Novel Curcuminoids - Abonia, Rodrigo; Laali, Kenneth K. (Synlett, 2025)
With the goal to overcome the bio-physicochemical drawbacks of parent curcumin (CUR) and to develop analogues with improved biological profiles and higher potencies, the present account provides a review summary of the work in my laboratory on the synthesis of structurally diverse libraries of curcuminoids (CURs), their in vitro bioassays, and computational docking studies. These efforts resulted in the discovery of a subset of compounds with exceptional antiproliferative and apoptotic activity that warrant further investigation. 1 Introduction2 Synthetic Strategies3 Bioassay Studies4 Computational Docking Studies5 Summary and Outlook
Keywords: novel curcuminoids; synthesis; in vitro bioassay; anticancer activity; computational docking